Involvement of Fcγ receptor polymorphism in the therapeutic response of idiopathic thrombocytopenic purpura - Fujimoto, Tetsuro‐Takahiro; Inoue, Maki; Shimomura, Takeshi; Fujimura, Kingo (British journal of haematology, 2001)
Clearance of autoantibody‐sensitized platelets through Fcγ receptors on phagocytic cells is one of the main mechanisms of thrombocytopenia in idiopathic thrombocytopenic purpura (ITP). We examined the FcγRIIA‐131R/H and FcγRIIIA‐158V/F polymorphisms in 104 adult chronic ITP patients, and in 59 healthy control subjects using polymerase chain reaction‐based allele‐specific restriction analysis. The frequency of FcγRIIA genotypes (131H/H, H/R, R/R) was not significantly different between patients and controls, and did not correlate with the responsiveness to treatment. In contrast, among FcγRIIIA genotypes, frequency of 158F/F homotype was smaller in ITP (P < 0·05). Furthermore, in FcγRIIIA‐158V/V homotype, the complete remission (CR) rate with medication (treatment with corticosteroid or other immunosuppressive agents) was significantly higher (60%) than that in 158V/F (10%) or 158V/F plus 158F/F, (P < 0·01, P < 0·05). Conversely, the CR rate after splenectomy in 158F/F and 158V/F types (64·3% and 54·6%) was higher than in 158V/V (25%). Our results indicate that the polymorphism of FcγRIIIA, but not FcγRIIA, influences the response to treatment in ITP.